Rapid synthesis of stable Cs2SnI6 double perovskite for visible-light DSSC–supercapacitor applications - Choon, Si Lin; Lim, Hong Ngee; Wan Mohd Abd Kalam, Wan Nadhirah; Ibrahim, Izwaharyanie; Ng, Chi Huey; Haw, Choon Yian; Mot, Augustin Catalin; Pop, Lucian Cristian (Elsevier, 2025)
Rapid synthesis of Cs2SnI6 is established by reacting the pre-prepared CsI and SnI4 via a mechanochemical approach, in which the reaction is stably conducted in a facile condition for 12 min with the incorporation of hydroiodic acid (HI). The Rietveld refinement analysis reveals that the synthesized Cs2SnI6 exhibits stable crystallinity for over 4 months under ambient conditions with a relative humidity of more than 70%, showing no significant changes in its purity. When incorporated into dye-sensitized solar cells (DSSCs), Cs2SnI6 exhibits a 32% enhancement in power conversion efficiency compared to the control, which is attributed to its superior light absorption and the matched energy levels of the device. The improved performance of DSSC employed with Cs2SnI6 is integrated with a supercapacitor and capable of photo-charging the device with a discharged specific capacitance of 92.12 F g-1 at 1 A g-1. The Cs2SnI6 DSSC-supercapacitor demonstrates twice the stability of the pristine device, with a retention rate of 81.27% under 1-sun illumination and a ≥ 60% stability improvement under halogen lamp illumination after 30 cycles, even without encapsulation. This study demonstrates, for the first time, the feasibility of Cs2SnI6 under visible light, highlighting its potential for future indoor energy applications.